Uso de nanopartículas de óxido de cinc como control de Omphalia flavida, agente causal de “la gotera”; enfermedad del cafeto (Coffea arábica L) (2021)
Since the 19th century, coffee has been the main agricultural export product in Colombia, guaranteeing an important contribution to the country's economic development. The disease called "The leak", caused by the fungus O. flavida (anamorphic phase of M. citricolor), occurs very frequently in coffee plants, whose main damage is defoliation. In the present study the in vitro characterization of the morphological and molecular variation of 16 and seven isolates of O. flavida, respectively; from four coffee producing municipalities in Cauca. Likewise, the in vitro pathogenicity of seven isolates in healthy coffee leaves of the Castillo® El Tambo Variety was determined, and finally the antifungal effect of ZnO-NPs was evaluated, specifically on two O. flavida isolates that presented a high level of pathogenicity. The results showed that the isolates were grouped into 4 morphotypes, according to the geographical area and the similarity of their morphological and cultural characteristics; accordingly, significant differences were found for the mycelial growth rate index (IVCM) except between the El Tambo and Bolívar isolates and (P = 0.351), there was no significant difference for the percentage of gems among the isolates evaluated by municipality (P=0.355), the vegetative and reproductive structures presented typical characteristics of the fungus, in addition significant differences were observed for the diameter of the head for both La Sierra and Caloto (P = 0.026), isolates, there were no differences in the length of the total pedicel of the gem for those isolates (P = 0.835) and there were differences in the total length of the gem for El Tambo and Caloto (P = 0.001) isolates. The high percentage of identity and the general BLASTn results indicated that the isolates would correspond to O. flavida. Regarding the evaluation of pathogenicity, the morphotypes of El Tambo and La Sierra had the highest levels of pathogenicity. The NPs based on ZnO showed an antifungal activity on the isolates that presented the highest levels of pathogenicity, the most efficient treatment was with 12 mmol.L